Боевой восемнадцатый год: (воен. действия Красной Армии в 1918 - начале 1919 г.) / А. Е. Антонов - Антонов Александр Ефимович (Воениздат, 1961)
Экземпляры: КХ (20120413) / Инвентарный номер: 290935 / Цена: 0.55 / Сис.шифр: 9(С)22 / Авт.знак: А 72 / ГРНТИ: 03 / ББК: 63